Endurance exercise training in pulmonary hypertension increases skeletal muscle electron transport chain supercomplex assembly. (May 2020) - McCullough, Danielle J.; Kue, Nouaying; Mancini, Thomas; Vang, Alexander; Clements, Richard T.; Choudhary, Gaurav
Pulmonary hypertension is associated with pronounced exercise intolerance (decreased V ċ O2 max) that can significantly impact quality of life. The cause of exercise intolerance in pulmonary hypertension remains unclear. Mitochondrial supercomplexes are large respiratory assemblies of individual electron transport chain complexes which can promote more efficient respiration. In this study, we examined pulmonary hypertension and exercise-induced changes in skeletal muscle electron transport chain protein expression and supercomplex assembly. Pulmonary arterial hypertension was induced in rats with the Sugen/Hypoxia model (10% FiO2, three weeks). Pulmonary arterial hypertension and control rats were assigned to an exercise training protocol group or kept sedentary for one month. Cardiac function and V ċ O2 max were assessed at the beginning and end of exercise training. Red (Type 1—oxidative muscle) and white (Type 2—glycolytic muscle) gastrocnemius were assessed for changes in electron transport chain complex protein expression and supercomplex assembly via SDS- and Blue Native-PAGE. Results showed that pulmonary arterial hypertension caused a significant decrease in V ċ O2 max via treadmill testing that was improved with exercise ( P < 0.01). Decreases in cardiac output and pulmonary acceleration time due to pulmonary arterial hypertension were not improved with exercise. Pulmonary arterial hypertension reduced expression in individual electron transport chain complex protein expression (NDUFB8 (CI), SDHB (CII), Cox IV (CIV), but not UQCRC2 (CIII), or ATP5a (CV)) in red gastrocnemius muscle. Both red gastrocnemius and white gastrocnemius electron transport chain expression was unaffected by exercise. However, non-denaturing Blue Native-PAGE analysis of mitochondrial supercomplexes demonstrated increases with exercise training in pulmonary arterial hypertension in the red gastrocnemius but not white gastrocnemius muscle. Pulmonary arterial hypertension-induced exercise intolerance is improved with exercise and is associated with muscle type specific alteration in mitochondrial supercomplex assembly and expression of mitochondrial electron transport chain proteins.